Pengaruh Word of Mouth, Store Atmosphere dan Harga terhadap Keputusan Pembelian Konsumen - Rika Antari, Desak Made; Wijaya, Putu Yudy; Wina Premayani, Ni Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aimed to investigate the effects of pricing, word-of-mouth, and warehouse atmosphere on partial and simultaneous purchasing choices. This study was carried out at Guwang Mart Guwang Traditional Village with a sample size of 100 individuals. There is a purposeful sampling. The present study employed a quantitative research design and employed various data analysis approaches, including classical assumptions, multiple linear regression, t tests, f tests, and instrument testing. The variables oral speaking, warehouse atmosphere, and price had a beneficial impact, according to the data. Additionally, the T test calculation shows that each variable, including the word-of-mouth and storage environment factors, has a partially positive and substantial impact. Furthermore, based on the T test calculation, each variable has a significant and favorable partial impact on price, shop atmosphere, and word-of-mouth. Based on the F test, the F-calculated value then concurrently has a positive and substantial effect. These initiatives are expected to improve customer happiness and service quality, make a better first impression, be more aesthetically pleasing, encourage clients to make recommendations on their own, maximise colour and lighting schemes, and maintain competitive pricing practices.